Improving Senior High School Students’ Physics Problem-solving Skills Through Investigated Based Multiple Representation (IBMR) Learning Model - Dyah Ayu Setyarini; Zainal Arifin Imam Supardi; Elok Sudibyo (IJORER : International Journal of Recent Educational Research, 2021)
This research aims to improve senior high school students’ physics problem-solving skills through learning used IBMR learning model. This research was a pre-an experimental study with a one-group pre-test and post-test design. The Methods of data collection used validation and test. The materials used to teach were valid category by two experts and can be used to practice physics problem-solving skills. The average post-test score physics problem-solving ability was 73.24 with an N-gain of 0.59 was classified as moderate. The success of IBMR learning model-based devices in practicing problem-solving abilities can be seen in the increase in the average score in each indicator of problem-solving abilities. The indicator of understanding the problem had the highest post-test average score of 94.58 with an N-gain of 0.89 in the high category. The problem-solving indicator had the lowest posttest average score was 58.22 with N-gain 0.39 and mean that it was the moderate category. Based on the results study, it can be concluded that the learning used by IBMR learning model can practice the ability to solve physics problems on heat material and its displacement. Learning with the IBMR learning model was expected to train students in solving physics problems. The stages in the IBMR learning model can help students